Identification of Research Growth and Decline in Countries Based on the Growth Rate of SCI Paper Citation Frequency - Kim, Suntae; Kim, Juseop (International Journal of Knowledge Content Development & Technology, 2025)
This study examines global research productivity, international collaboration, and citation growth trends from 1980 to 2023 using Web of Science data. Bibliometric analysis assessed national publication shares, collaboration rates, and five-year average citations per paper. Regression and correlation analyses explored relationships between these variables, while publication trends across 22 fields identified significant national research growth or decline. Findings reveal a weak negative correlation (-0.3937 to -0.0935) between research productivity and collaboration. China, South Korea, and Saudi Arabia showed increased publication shares, while the United States and Japan declined. Singapore and Estonia exhibited strong citation growth, whereas the United States maintained high citation counts despite slower growth. Russia excelled in microbiology and engineering, while the United States and Luxembourg saw declines in multiple fields. The study’s reliance on Web of Science data may underrepresent certain regions or disciplines, and qualitative aspects of collaboration were not assessed. Future research should integrate broader data sources. This research informs national strategies, investment decisions, and global partnerships. By identifying research trends, it supports policy decisions influencing economic and technological progress, highlighting the role of science in national development.